Effects of the moderate CYP3A4 inhibitor, fluconazole, on the pharmacokinetics of fesoterodine in healthy subjects - Malhotra, Bimal; Dickins, Maurice; Alvey, Christine; Jumadilova, Zhanna; Li, Xiaoxi; Duczynski, Gregory; Gandelman, Kuan (British journal of clinical pharmacology, 2011)
WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • Available data suggest that fesoterodine dosage should not exceed 4 mg once daily when taken concomitantly with potent CYP3A4 inhibitors, such as ketoconazole. Currently, no information is available on whether dose adjustment is necessary when fesoterodine is administered with a moderate CYP3A4 inhibitor. WHAT THIS STUDY ADDS • This study shows that adjustment of fesoterodine dose is not warranted when co‐administered with a moderate CYP3A4 inhibitor. AIMS To assess the effects of fluconazole, a moderate CYP3A4 inhibitor, on the pharmacokinetics (PK) and safety/tolerability of fesoterodine. METHODS In this open‐label, randomized, two‐way crossover study, 28 healthy subjects (18–55 years) received single doses of fesoterodine 8 mg alone or with fluconazole 200 mg. PK endpoints, including the area under the plasma concentration–time curve from 0 to infinity (AUC(0,∞)), maximum plasma concentration (Cmax), time to Cmax (tmax), and half‐life (t1/2), were assessed for 5‐hydroxymethyl tolterodine (5‐HMT), the active moiety of fesoterodine. RESULTS Concomitant administration of fesoterodine with fluconazole increased AUC(0,∞) and Cmax of 5‐HMT by approximately 27% and 19%, respectively, with corresponding 90% confidence intervals of (18%, 36%) and (11%, 28%). There was no apparent effect of fluconazole on 5‐HMT tmax or t½. Fesoterodine was generally well tolerated regardless of fluconazole co‐administration, with no reports of death, serious adverse events (AEs) or severe AEs. Following co‐administration of fesoterodine with fluconazole, 13 subjects (48%) experienced a total of 40 AEs; following administration of fesoterodine alone, six subjects (22%) experienced a total of 19 AEs. The majority of AEs were of mild intensity. There were no clinically significant changes in laboratory or physical examination parameters. CONCLUSION Fesoterodine 8 mg single dose was well tolerated when administered alone or with fluconazole. Based on the observed increase in 5‐HMT exposures being within the inherent variability of 5‐HMT pharmacokinetics, adjustment of fesoterodine dose is not warranted when co‐administered with a moderate CYP3A4 inhibitor provided they are not also inhibitors of transporters.